Urinary renin in patients and mice with diabetic kidney disease - Tang, Jeannette (2019)
In patients with diabetic kidney disease (DKD), plasma renin activity is usually decreased, but there is limited information on urinary renin and its origin. Urinary renin was evaluated in samples from patients with longstanding type I diabetes mellitus and mice with streptozotocin-induced diabetes mellitus. Renin-reporter mouse model (Ren1d-Cre;mT/ mG) was made diabetic with streptozotocin to examine whether the distribution of cells of the renin lineage was altered in a chronic diabetic environment. Active renin was increased in urine samples from patients with DKD (n=36), compared with those without DKD (n=38; 3.2 versus 1.3 pg/mg creatinine; P<0.001). In mice with streptozotocin-induced diabetes mellitus, urine renin was also increased compared with nondiabetic controls. By immunohistochemistry, in mice with streptozotocin-induced diabetes mellitus, juxtaglomerular apparatus and proximal tubular renin staining were reduced, whereas collecting tubule staining, by contrast, was increased. To examine the role of filtration and tubular reabsorption on urinary renin, mice were either infused with either mouse or human recombinant renin and lysine (a blocker of proximal tubular protein reabsorption). Infusion of either form of renin together with lysine markedly increased urinary renin such that it was no longer different between nondiabetic and diabetic mice. Megalin mRNA was reduced in the kidney cortex of streptozotocin-treated mice (0.70±0.09 versus 1.01±0.04 in controls, P=0.01) consistent with impaired tubular reabsorption. In Ren1d-Cre;mT/mG with streptozotocin-induced diabetes mellitus, the distribution of renin lineage cells within the kidney was similar to nondiabetic renin-reporter mice. No evidence for migration of cells of renin linage to the collecting duct in diabetic mice could be found. Renin mRNA in microdissected collecting ducts from streptozotocin-treated mice, moreover, was not significantly different than in controls, whereas in kidney cortex, largely reflecting juxtaglomerular apparatus renin, it was significantly reduced. In conclusion, in urine from patients with type 1 diabetes mellitus and DKD and from mice with streptozotocin-induced diabetes mellitus, renin is elevated. This cannot be attributed to production from cells of the renin lineage migrating to the collecting duct in a chronic hyperglycemic environment. Rather, the elevated levels of urinary renin found in DKD are best attributed to altered glomerular filteration and impaired proximal tubular reabsorption.